A Theory of Knowledge Management - Syed Aktharsha, U. (Journal of Contemporary Research in Management (JCRM), 2013)
Knowledge is an important organizational resource. Unlike other inert organizational resources, the application of existing knowledge has the potential to generate new knowledge. Not only can knowledge be replenished in use, it can also be combined and recombined to generateÂ new knowledge. Once created, knowledge can be articulated, shared, stored, and re-contextualized to yield options for the future. For all of these reasons, knowledge has the potential to be applied across time and space to yield increasing returns (Garud & Kumaraswamy, 2005). The strategic management of organizational knowledge is a key factor that can help organizations to sustain competitive advantage in volatile environments. Organizations are turning to knowledge management initiatives and technologies to leverage their knowledge resources. Knowledge management can be defined as a systemic and organizationally specified process for acquiring, organizing, and communicating knowledge of employees so that other employees may make use of it to be more effective and productive in their workÂ (Kankanhalli, Tan, & Wei, 2005). Knowledge management is also important in inter organizational relationships. This article attempts to explain the theoretical framework of knowledge and knowledgeÂ management in terms of knowledge characteristics, Knowledge categories, Knowledge value level and Knowledge Needs identification.